2017
DOI: 10.1021/acs.joc.6b02781
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzimidazolones via One-Pot Reaction of Hydroxylamines, Aldehydes, and Trimethylsilyl Cyanide Promoted by Diacetoxyiodobenzene

Abstract: A novel and efficient PhI(OAc)-promoted one-pot reaction of aromatic hydroxylamines, aldehydes, and TMSCN in the presence of BF·EtO is described. A wide variety of N-substituted benzimidazolones are obtained with satisfactory yields under mild reaction conditions. The method was proven to be efficient for the synthesis of benzimidazolone derivatives from readily available starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In order to improve the electrical and electro-optic properties of LC materials, great efforts have been made to attach C 60 covalently to mesogens as well as to dope C 60 into LC matrices [95,[202][203][204]. The recent, significant developments in fullerene-containing LCs have been reviewed by Zhang et al [205].…”
Section: Modification Of Physical Properties Of Lc Materials By Nanodmentioning
confidence: 99%
“…In order to improve the electrical and electro-optic properties of LC materials, great efforts have been made to attach C 60 covalently to mesogens as well as to dope C 60 into LC matrices [95,[202][203][204]. The recent, significant developments in fullerene-containing LCs have been reviewed by Zhang et al [205].…”
Section: Modification Of Physical Properties Of Lc Materials By Nanodmentioning
confidence: 99%
“…Hypervalent iodine­(III) compounds have attracted much attention as oxidants in organic synthesis, as they can be a replacement for transition metals with the advantage of having environmentally benign properties. Although iodine­(III) reagents are competent to conduct many organic transformations, addition of a Lewis acid such as BF 3 is often a prerequisite for a process to occur. For example, it has been shown that an iodine­(III) reagent in conjunction with BF 3 ·Et 2 O considerably accelerates the processes that yield λ 3 -diaryliodanes, olefin diacetoxylation, and a plethora of other products. In this context, Ochiai et al reported that alcohols can be selectively oxidized by hypervalent iodine­(III) compound 2 to aldehydes or ketones in the presence of BF 3 ·Et 2 O as the catalyst (Scheme ). For this catalytic reaction, the first step is proposed to be a ligand exchange between iodine­(III) reagent 2 and the alcohol, followed by a redox process to give the final product.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic methods of benzimidazolone can be classied into 6 types (Scheme 2). 14,15 Firstly, benzimidazolone is commonly synthesized by cyclocarbonylation of ortho-substituted anilines 1 and various carbonyl reagents according to related references. For example, Bhanage et al 16 reported that benzimidazolone was obtained in 98% yields from the reaction of urea with 1,2-diaminobenzene without any catalysts under a reduced pressure.…”
Section: Synthesis Of Benzimidazolonementioning
confidence: 99%